Pemanfaatan Data Mining Dalam Memprediksi Produksi Pada PT Pupuk Sriwidjaja Palembang Menggunakan Algoritma Regresi Liniear Berganda - Adji Dwi Alfarizi; Andri Andri (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
PT.Pupuk Sriwidjaja Palembang is a company that has the main task in the production and marketing of urea fertilizer and npk fertilizer. Production estimates are needed so that companies can determine strategies and breathrought so that the production process runs optimally. This study discusses the application of data mining in predicting the production of NPK Fertilizer Formula 15-15-15 PSO at PT.Pupuk Sriwidjaja Palembang. In its application, this research uses the multiple Linear Regression Algorithm by utilizing production history data for the 2019-2020 period. If you have already mined the production history data for the 2019-2020 period, there will bi predictions in 2021 which are predicted by the rapidminer application and using a multiple linear regression algorithm, which produces a predicted value of fertilizer production in 2021 as much as 70800 tons.